Inteligencia emocional y relaciones interpersonales en estudiantes del nivel secundario del colegio Experimental UNAP, San Juan Bautista 2022 - Yomona Perez, Paulo Ramiro (2024)
The purpose of the study was to verify the connection of emotional intelligence with interpersonal relationships in high school students of the UNAP Experimental School, San Juan Bautista 2022. A confirmatory quantitative methodology was assumed with a relational and transectional descriptive design with a sample of 204 subjects selected proportionally and through stratified random sampling; Two questionnaires were used to measure the study variables. The findings showed that the students have high emotional intelligence (35.3%); medium (50.0%) and low (14.7%). Regarding interpersonal relationships, a high (34.3%), medium (50.0%) and low (15.7%) level was determined. Using Spearman's Rho, it was possible to verify that there is a relevant connection between emotional intelligence and interpersonal relationships (rs = 0.781), p <0.05; coinciding with the general hypothesis of the study. It was also revealed that there is an important connection between emotional intelligence and family ties (rs=0.591), p <0.05; coinciding with the first specific hypothesis of the study. Similarly, it was determined that emotional intelligence is significantly linked to relationships with the opposite sex (rs=0.589), p <0.05; with which the second specific hypothesis was accepted. Finally, emotional intelligence was significantly related to the school connections dimension (rs=0.589), p <0.05; with which the third specific hypothesis formulated is accepted.